Approaches to pandemic prevention – the chromatin vaccine - Zhang, Jielin; Askenase, Philip; Jaenisch, Rudolf; Crumpacker, Clyde S. (Frontiers in Immunology, 2023)
Developing effective vaccines against viral infections have significant impacts on development, prosperity and well-being of human populations. Thus, successful vaccines such as smallpox and polio vaccines, have promoted global societal well-being. In contrast, ineffective vaccines may fuel arguments that retard scientific progress. We aim to stimulate a multilevel discussion on how to develop effective vaccines against recent and future pandemics by focusing on acquired immunodeficiency syndrome (AIDS), coronavirus disease (COVID) and other viral infections. We appeal to harnessing recent achievements in this field specifically towards a cure for current pandemics and prevention of the next pandemics. Among these, we propose to apply the HIV DNA in chromatin format -an end product of aborted HIV integration in episomal forms, i.e., the chromatin vaccines (cVacc), to elicit the epigenetic silencing and memory that prevent viral replication and infection.